2016
DOI: 10.5194/tc-10-1513-2016
|View full text |Cite
|
Sign up to set email alerts
|

Arctic sea-ice diffusion from observed and simulated Lagrangian trajectories

Abstract: Abstract. We characterize sea-ice drift by applying a Lagrangian diffusion analysis to buoy trajectories from the International Arctic Buoy Programme (IABP) dataset and from two different models: the standalone Lagrangian sea-ice model neXtSIM and the Eulerian coupled ice-ocean model used for the TOPAZ reanalysis. By applying the diffusion analysis to the IABP buoy trajectories over the period 1979-2011, we confirm that sea-ice diffusion follows two distinct regimes (ballistic and Brownian) and we provide accu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
(57 reference statements)
3
11
0
Order By: Relevance
“…Nevertheless, overall, our findings based on the modeled trajectories herein (Tables 3-5; Supplementary Tables S1-S4 1 ), as measured by the ratio of modeled to observed path lengths (indicative of relative speed) and skill scores, are consistent with Rampal et al's (2016b) findings related to relative performance. A comprehensive test series involving statistical comparisons of the modeled trajectories to approximately four hundred 5, 10, 15, and 30 day intervals of IABP drifter trajectories demonstrated that the new neXtSIM model predictions agree more closely with the observations than the operational status quo models represented by TOPAZ4 using the older (standard) EVP rheology.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…Nevertheless, overall, our findings based on the modeled trajectories herein (Tables 3-5; Supplementary Tables S1-S4 1 ), as measured by the ratio of modeled to observed path lengths (indicative of relative speed) and skill scores, are consistent with Rampal et al's (2016b) findings related to relative performance. A comprehensive test series involving statistical comparisons of the modeled trajectories to approximately four hundred 5, 10, 15, and 30 day intervals of IABP drifter trajectories demonstrated that the new neXtSIM model predictions agree more closely with the observations than the operational status quo models represented by TOPAZ4 using the older (standard) EVP rheology.…”
Section: Discussionsupporting
confidence: 79%
“…A comprehensive test series involving statistical comparisons of the modeled trajectories to ∼400 intervals of 5, 10, 15, and 30 days from IABP drifter trajectories demonstrated that the new neXtSIM model predictions agree more closely with the observations than the operational status quo models represented by TOPAZ4 using the older (standard) EVP rheology, in agreement with findings by Rampal et al (2016b). However, all of the models performed well in operational mode where the modeled locations are updated regularly (every 5 days) with locations of field-deployed drifters.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Single-particle dispersion also provides a signature of Lévy dynamics (Schlesinger et al, 1993) or processes associated with intermittent "flight" (anomalous or ballistic transport) and "trapping" events, such as are observed in directional changes in the ice cover explored in the present investigation. Previous studies have illustrated the use of Lagrangian dispersion statistics to quantify dynamical regimes in the ice cover (Rampal et al, 2009a,b;Lukovich et al, 2011Lukovich et al, , 2015Rampal et al, 2016). In this study, we build upon previous analyses by identifying inflection points in total absolute dis- persion results to identify transitions in distinct dynamical regimes.…”
Section: Methodsmentioning
confidence: 97%